2011
DOI: 10.3109/0886022x.2011.605531
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function and Histological Damage in Autopsy Subjects with Myocardial Infarction

Abstract: Objectives: Chronic kidney disease (CKD) is a major risk factor for cardiovascular disease (CVD). We previously reported renal parenchymal damage in autopsy subjects with stroke or abdominal aortic aneurysm. The aim of this study is to evaluate the relationship between renal histology and clinical characteristics of patients with myocardial infarction (MI). Methods: A total of 699 subjects were autopsied at the National Cerebral and Cardiovascular Center Hospital. We retrospectively evaluated all autopsy cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Kidneys that suffer histological damage show declining renal function 26 . Our study supports this statement with results showing that eGFR was significantly different between the different categories of histology.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Kidneys that suffer histological damage show declining renal function 26 . Our study supports this statement with results showing that eGFR was significantly different between the different categories of histology.…”
Section: Discussionsupporting
confidence: 89%
“…Kidneys that suffer histological damage show declining renal function. 26 Our study supports this statement with results showing this increases renal cortical stiffness, which, in turn, increases YM measurements. 28 Our results also found that SWE imaging was able to distinguish between the <25% and 25%-50% groups, as well as between the <25% and >50% groups of interstitial fibrosis and tubular atrophy.…”
Section: Discussionsupporting
confidence: 88%
“…Accelerated and progressive decline in renal function is common and associated with increased mortality in MI patients during hospitalization [1,2]. Renal parenchymal damage is closely associated with deteriorating renal function following MI [3,4]. Therefore, it is of paramount importance to explore potential mechanisms involved in renal parenchymal damage in order to prevent the onset and progression of renal dysfunction after the initiation of MI with subsequent CHF.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present patient had no hypertension or diabetes and was 31 years of age. Although considered in the autopsies of persons who died from myocardial infarction, histological changes (such as arteriolar hyalinosis and arteriosclerosis of medium-sized arteries) are strongly associated with the renal function and proteinuria (10).…”
Section: Discussionmentioning
confidence: 99%